How to promote changes in primary care? The Florentine experience of the House of Community - Milani, Chiara; Naldini, Giulia; Baggiani, Lorenzo; Nerattini, Marco; Bonaccorsi, Guglielmo (Frontiers in Public Health, 2023)
Primary care (PC) has a central role in promoting health and preventing diseases, even during health emergencies. COVID-19 pandemic has shown how strengthening comprehensive primary health care (c-PHC) services is key in warranting community health. The Italian government decided to support PHC by investing resources of Next Generation EU (NextGenEu) plan on the development of the Local Health Districts (LHD) and local PC centres called “Houses of Community (HoC)”. The Florence LHD (Tuscany) - in direct collaboration with the University of Florence - has represented the experimental context in which c-PHC inspired organizational model has been proposed and included the HoC as the nearest access point to PC services. The HoCs provide continuity of care and health and social integration, through multiprofessional collaborative practices. Different levels of action must coexist in order to initiate, implement and make this new PC model sustainable: the organizational and managerial level, the experimentation of new model of care and the research level, involving universities and LHD, through participative approaches of research and action. This process benefits from health professionals (HPs) participation and continuous assessment, the caring for the working relationships among HPs and services, an appropriate research methodology together with a “permeable” multidisciplinary research group, and educational programs. In this context, the HoC assumes the role of a permanent laboratory of experimentation in PC, supporting the effectiveness of care and answering to what Next Gen EU plan has been foreseeing for the rethinking of Italian territorial services.